The Effect of Principal Management on Teacher Teaching Performance in Schools - Anang Dwi Ujianto (Tadbir : Jurnal Studi Manajemen Pendidikan, 2022)
This study aims to describe the influence of principal management on the teaching performance of teachers in SMA Negeri 1 Pasirian. The research method uses quantitative research with 30 teachers teaching at SMA Negeri 1 Pasirian, Lumajang, East Java. Data collection techniques were carried out using a questionnaire. Descriptive analysis of the data was carried out by calculating the average, percentage, and calculating the score category criteria for each variable. This research uses linearity test with ANOVA calculation, correlation calculation with product moment formula, and significance calculation using t test. The results of this study indicate an average score of 72% is included in the good category in the management of the principal's management. Meanwhile, for the management of teacher teaching performance, the average score of 76.55% is included in the good category. Furthermore, the contribution of principal management to the teaching performance of teachers is 16.5%. The calculation of significance shows that t count = 2,349 > 2,048 t table at significance level = 0,5 so it can be concluded that there is a significant influence between principal management on teacher teaching performance which means that the better the leadership performance of the principal, the better the teacher's performance at SMA Negeri 1 Pasirian.